Hubungan Motivasi dan Hasil Belajar Siswa Kelas XI MAN Model Makassar - Nur Yuliany (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2019)
This study discusses the correlation between students’ learning motivation and mathematics learning outcomes. The population of this study is 320 students of class XI MAN Model Makassar. The technique sampling used was random sampling. Data collected by using documentation format and questionnaire. Data analyzed by using descriptive analysis and nonparametric statistical analysis. The result of descriptive analysis showed that 53,75% of students had high learning motivation and 62,5% of students get scores 7-7,4 on 10 scales. The result of nonparametric statistic analysis showed that the coefficient correlation between learning outcomes and motivation was 0,522 by the Kendall test and 0,575 by Spearman test. T = 5,405 by Kendall and t = 6, 208 by Spearman was greater than t table 2,326. It means that there were a positive and significant correlation between students’ motivation and learning outcomes.